(untitled) (Schermi. Storie e culture del cinema e dei media in Italia, 2022)
In the present essay, I will investigate the role of censorship in Italian Mondo films made in the 1960s and 1970s, such as Africa addio (1966, Gualtiero Jacopetti, Franco Prosperi), Africa segreta (1969, Angelo Castiglioni, Alfredo Castiglioni, Guido Guerrasio), Africa ama (1971, Angelo Castiglioni, Alfredo Castiglioni, Guido Guerrasio). In particular, I will focus my analysis on the works made by Angelo and Alfredo Castiglioni with Guido Guerrasio. In addition to their relationship with censorship boards, their film – despite some similarities with Mondo genre – demonstrates the attempt to elaborate a different projectin the subgenre dedicated to the African continent.